2014
DOI: 10.1002/cne.23548
|View full text |Cite
|
Sign up to set email alerts
|

Localization of tyrosine hydroxylase‐like immunoreactivity in the nervous systems of Biomphalaria glabrata and Biomphalaria alexandrina, intermediate hosts for schistosomiasis

Abstract: Planorbid snails of the genus Biomphalaria are major intermediate hosts for the digenetic trematode parasite Schistosoma mansoni. Evidence suggests that levels of the neurotransmitter dopamine (DA) are reduced during the course of S. mansoni multiplication and transformation within the snail. This investigation used immunohistochemical methods to localize tyrosine hydroxylase (TH), the rate-limiting enzyme in the biosynthesis of catecholamines, in the nervous system of Biomphalaria. The two species examined, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 28 publications
(52 citation statements)
references
References 116 publications
2
42
1
Order By: Relevance
“…and in four to six small neurons near the origin of the T n. (Figure a,d, arrows ). As reported by Vallejo et al (), the T n. also contained a bundle of THli fibers that originated from small peripheral cells in the tentacle epithelium. The THli fiber bundle was more compact than the GABAli axons and occupied a distinct portion of the nerve (Figure b,e).…”
Section: Resultssupporting
confidence: 71%
See 3 more Smart Citations
“…and in four to six small neurons near the origin of the T n. (Figure a,d, arrows ). As reported by Vallejo et al (), the T n. also contained a bundle of THli fibers that originated from small peripheral cells in the tentacle epithelium. The THli fiber bundle was more compact than the GABAli axons and occupied a distinct portion of the nerve (Figure b,e).…”
Section: Resultssupporting
confidence: 71%
“…A previous study showed that prominent THli fiber systems in the lip nerves originate predominantly from peripheral neurons (Vallejo et al, ). A group of THli central neurons was observed in the anterolateral region the cerebral ganglion, however (Figure e,h, arrowheads) , prompting double‐labeling experiments to test for the presence of GABA‐TH colocalization.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…mansoni larvae, the larvae could, in turn. also affect the snails through aminergic pathways as suggested by Delgado et al [34] and Vallejo et al [35]. For example, serotonin may be involved in parasitic castration [67], leading to a redirection of energy resources in infected snails [68][69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%